2016
DOI: 10.1007/s11695-016-2492-6
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Ameliorates Diabetic Cardiac Dysfunction by Inhibiting ER Stress in a Diabetic Rat Model

Abstract: DJB and SG ameliorated cardiac dysfunction by inhibiting PERK-mediated pathway. And no difference was observed on the effects of DJB and SG on ER stress-dependent myocardium damage in diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…However, there has been limited study regarding the therapeutic effects of DJB on DCM to date. Our previous research showed that DJB could ameliorate diabetic cardiac dysfunction in a rat model. However, more studies are required to elucidate the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been limited study regarding the therapeutic effects of DJB on DCM to date. Our previous research showed that DJB could ameliorate diabetic cardiac dysfunction in a rat model. However, more studies are required to elucidate the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it serves a key function in the pathogenesis and progression of DCM. Accumulating evidence has indicated that cardiomyocyte endoplasmic reticulum (ER) stress is involved in the pathogenesis of cardiac dysfunction in patients with DM and animal models (8,9). The early stages of ER stress are considered to be an adaptive response aiming at maintenance of ER homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…If it persists long-term, ER stress could induce the intrinsic pathway of apoptosis (11). C/EBP homologous protein (CHOP), a marker of ER stress, was identified to be elevated in multiple organs of a diabetic animal model, including myocardial tissue (9,12,13). Furthermore, CHOP knockout mice were observed to exhibit less pronounced hypertrophy and cardiac dysfunction in comparison with wild-type animals (14).…”
Section: Introductionmentioning
confidence: 99%
“…As a novel therapy, bariatric surgery has been demonstrated to provide rapid and sustained remission in type 2 diabetes mellitus (T2DM) and associated complications (32,34). It has attracted increasing attention because of its effectiveness in alleviating diabetic cardiac dysfunction (17,46), which was reported to be independent of weight loss or dietary changes (13). However, the underlying mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the effect of bariatric surgery on myocardial Ca 2ϩ homeostasis has not been reported. Our previous study (46) showed that bariatric surgery could ameliorate myocardial SR stress in diabetic rats by inhibiting the protein kinase R-like endoplasmic reticulum kinase-mediated signaling pathway. Given that the SR is the storage site for Ca 2ϩ and modulation of SR stress is a large benefit to normalize the perturbed Ca 2ϩ homeostasis (39,45), it raises the hypothesis that the alleviation of DCM after bariatric surgery may be associated with facilitated myocardial Ca 2ϩ homeostasis.…”
Section: Introductionmentioning
confidence: 99%